Antimicrobial Activity of Leaf Aqueous Extract of Schinus Polygamus (Cav.) Cabrera Against Pathogenic Bacteria and Spoilage Yeasts - Ganga-Munoz, M; Bruna-Bugueno, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The antimicrobial activity of an aqueous extract of the leaves of Schinus polygamus (cav.) Cabrera against microorganisms of food importance was evaluated. First, the leaf aqueous extract of Schinus polygamus was characterized, quantifying hydroxycinnamic acids and phenolic compounds. Then, a battery of strains was tested, including Escherichia coli ATCC 25922, Salmonella Typhimurium ATCC 14028, and Listeria monocytogenes ATCC 13932. Also, we tested wine spoilage yeasts such as Brettanomyces bruxellensis LAMAP2480, B. bruxellensis LAMAP1359, B. bruxellensis CECT1451, and Pichia guilliermondii NPCC1051. Tests were conducted using the kinetic curve of growth and cell viability counts. The results indicate that with 10% v/v of concentrated extract, it is possible to observe growth inhibition of all microorganisms studied, with statistically significant differences during the whole measurement time (70 h for bacteria and 145 h for yeast). © 2024 by the authors.